Operating Results of Department Store Chains and Department Store Ownership Groups (Book). - Gault, Edgar H. (The Accounting Review, 1936)
Reviews the book "Operating Results of Department Store Chains and Department Store Ownership Groups, 1929, 1931-1934," by Stanley F. Teele.